If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(y-4)-3(5y+1)=3(y-2)-4(2y+1)
We move all terms to the left:
7(y-4)-3(5y+1)-(3(y-2)-4(2y+1))=0
We multiply parentheses
7y-15y-(3(y-2)-4(2y+1))-28-3=0
We calculate terms in parentheses: -(3(y-2)-4(2y+1)), so:We add all the numbers together, and all the variables
3(y-2)-4(2y+1)
We multiply parentheses
3y-8y-6-4
We add all the numbers together, and all the variables
-5y-10
Back to the equation:
-(-5y-10)
-8y-(-5y-10)-31=0
We get rid of parentheses
-8y+5y+10-31=0
We add all the numbers together, and all the variables
-3y-21=0
We move all terms containing y to the left, all other terms to the right
-3y=21
y=21/-3
y=-7
| 6(x)-4=-10 | | -2=3+m/2 | | -4(3x+5)=19 | | −3(−2a−4)+25=−3(5a+9)+1. | | 6+16(x−2)=x−29 | | 13x+13=7x-4 | | 7n+6=4n-9n= | | r/4+ 15=18 | | r4+ 15=18 | | 5(5y-2)+3(2y+6)=25(3y+2)-14y | | h/4− 2=2 | | x+1.3=2.25 | | 14x+14+13x+13=180 | | (k+4)(k-4)=9 | | -5(-4x+7)=3 | | 13x+13+14x+14=180 | | 16(x+3)=8(x-5)-5(x+4)-9 | | -7y+3(y-6)=-14 | | -12=-8z+18 | | -15+3x/7x=-43 | | -7y+3(y-6=-14 | | 25x=40+x | | 4=174-u | | -6x+2(x+6)=20 | | (4x+6)°+(11x-6)°=180 | | 2x^2(6x-8)+4=39 | | 286=-x+224 | | 4+2(z−7)=−3(3+z)+4z−2 | | -3=2/3(-1)+x | | 18x+3=15x+2 | | 8(w-4)-4w=-16 | | (5r+20)/15=(4r-24)/4 |